Non-prescription treatments for childhood infections: an Austrian, monocentric, cross-sectional questionnaire study - Matthias Gerlitz; Peter Voitl; Julian J. M. Voitl; Susanne C. Diesner-Treiber (BMC, 2022)
Abstract Background Infectious diseases like the common cold, otitis media, or gastroenteritis frequently occur in childhood. In addition to prescription drugs, parents often use supplementary over-the-counter (OTC) products recommended by pharmacists and other non-medical professionals to relieve their children's symptoms. However, the efficacy of such alternative treatments lacks conclusive evidence. The objective of this study was to investigate the use of OTC products and related active ingredients in children, and the motivations behind this choice. Methods The present study included 215 children aged between 1 and 14 years with an acute respiratory tract infection, e.g., common cold, bronchitis, otitis media, tonsillitis, or gastroenteritis. During their visit to the pediatric practice, parents filled in a self-administered questionnaire about their child's diagnosis, additional treatment options, and motivations to integrate supplementary medicinal products after their first visit for acute infection or follow-up examination. Children with chronic illnesses and patients visiting for a routine maternal and child health program check-up were excluded. Results The study included 111 (51.6%) males and 104 (48.4%) females. Median age was 3.00 (IQR 2.0 - 5.0) years. The most common reason for a visit was a respiratory tract infection (78.6%). Out of 215 parents, 182 (84.7%) resorted to non-prescription remedies to alleviate their child's symptoms. Teas (45.1%), and home remedies (43.3%) were the most popular. At total 133 (74.3%) followed recommendations from friends and family regarding additional medications usage. Parents with previous experience with complementary medicine tended to prefer this approach to treat their children (p.adjust = 0.08). Conclusion The use of non-prescription medicine is increasing as well as the range of related information sources. Evidence-based recommendations in this field might improve pediatric care.